Pregnancy and neonatal outcomes of COVID-19: co-reporting of common outcomes from PAN-COVID and AAP SONPM registries - Mullins,E; Hudak,ML; Banerjee,J; Getzlaff,T; Townson,J; Barnette,K; Playle,R; Bourne,T; Lees,C; PAN-COVID,investigators and the National Perinatal COVID-19 Registry Study Group (Ultrasound in Obstetrics and Gynecology, 2021)
OBJECTIVE: Few large cohort studies have reported data on maternal, fetal, perinatal and neonatal outcomes associated with SARS-CoV-2 infection in pregnancy. We report the outcome of infected pregnancies from a collaboration formed early during the pandemic between the investigators of two registries, the UK and global Pregnancy and Neonatal outcomes in COVID-19 (PAN-COVID) study and the US American Academy of Pediatrics Section on Neonatal Perinatal Medicine (AAP SONPM) National Perinatal COVID-19 Registry. METHODS: This was an analysis of data from the PAN-COVID registry (January 1st to July 25th 2020), which includes pregnancies with suspected or confirmed maternal SARS-CoV-2 infection at any stage in pregnancy, and the AAP SONPM National Perinatal COVID-19 registry (April 4th to August 8th 2020), which includes pregnancies with positive maternal testing for SARS-CoV-2 from 14 days before delivery to 3 days after delivery. The registries collected data on maternal, fetal, perinatal and neonatal outcomes. The PAN-COVID results are presented both overall for pregnancies with suspected or confirmed SARS-CoV-2 infection and separately in those with confirmed infection. RESULTS: We report on 4005 pregnant women with suspected or confirmed SARS-CoV-2 infection (1606 from PAN-COVID and 2399 from AAP SONPM). For obstetric outcomes, in PAN-COVID overall, those with confirmed infection in PAN-COVID and AAP SONPM, respectively, maternal death occurred in 0.5%, 0.5% and 0.2% of cases, early neonatal death in 0.2%, 0.3% and 0.3% of cases and stillbirth in 0.5%, 0.6% and 0.4% of cases. Delivery was pre-term (<37 weeks' gestation) in 12.0% of all women in PAN-COVID, in 16.2% of those women with confirmed infection in PAN-COVID and in 15.7% of women in AAP SONPM. Extremely preterm delivery (< 27 weeks' gestation) occurred in 0.5% of cases in PAN-COVID and 0.3% in AAP SONPM. Neonatal SARS-CoV-2 infection was reported in 0.8% of all deliver